Adipose Mesenchymal Stem Cell-Derived Exosomes as Nanocarriers for Treating Musculoskeletal Disorders - Tang A; Shu Q; Jia S; Lai Z; Tian J (International Journal of Nanomedicine)
Ao Tang,1,2,* Qing Shu,1,2,* Shaohui Jia,2 Zhihao Lai,1 Jun Tian1 1Department of Rehabilitation Medicine, Zhongnan Hospital of Wuhan University, Wuhan, People’s Republic of China; 2College of Sports Medicine, Wuhan Sports University, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Tian, Institute/University/Hospital: Zhongnan Hospital of Wuhan University, Street Name & Number: No. 169, Donghu Road, Wuchang District, Wuhan City, Hubei Province, 430079, People’s Republic of China, Tel +86 02767813170, Email tianjun@znhospital.cnAbstract: Musculoskeletal disorders are a series of diseases involving bone, muscle, cartilage, and tendon, mainly caused by chronic strain, degenerative changes, and structural damage due to trauma. The disorders limit the function of patients due to pain and significantly reduce their quality of life. In recent years, adipose-derived mesenchymal stem cells have been extensively applied in regeneration medicine research due to their particular abilities of self-renewal, differentiation, and targeted homing and are more easily accessed compared with other sources. The paracrine effect of ADSCs plays a crucial role in intercellular communication by releasing mass mediators, including cytokines and growth factors, particularly the exosomes they secrete. Not only do these exosomes possess low immunogenicity, low toxicity, and an enhanced ability to penetrate a bio-barrier, but they also inherit their parent cells’ characteristics and carry various bioactive molecules to release to targeted cells, modulating their biological process. Meanwhile, these characteristics also make exosomes a natural nanocarrier capable of targeted drug delivery to specific sites, enhancing the bioavailability of drugs within the body and achieving precision therapy with fewer toxic side effects. Furthermore, the integration of exosomes with tissue engineering and chemical modification strategies can also significantly enhance their efficacy in facilitating tissue repair. However, the current research on ADSC-Exos for improving MSDs remains at an early stage and needs further exploration. Therefore, this review summarized the ADSC-Exo as a nanodrug carrier characteristics and mechanism in the treatment of fracture, osteoporosis, osteoarthritis, intervertebral disc degeneration, and tendon injury, which push forward the research progress of ADSC-Exo therapy for MSDs.Keywords: exosomes, adipose mesenchymal stem cells, musculoskeletal disorders, regenerative medicine